Factors Influencing the High Acceptance of Injectable Contraceptives - Rifzul Maulina; Dian Setyorini (Health and Technology Journal (HTechJ), 2026)
The use of injectable contraceptives remains the leading choice among women of reproductive age (WRA) in various regions in Indonesia. The number of injectable family planning (FP) acceptors has increased significantly compared to other contraceptive methods. This study aims to describe and analyze the factors influencing the high number of injectable contraceptive acceptors. This research employed a descriptive, cross-sectional design. The study population consisted of all active injectable contraceptive acceptors (35 respondents), selected using a total sampling technique. Data were analyzed descriptively using frequency and percentage distribution. The results showed that most respondents had good knowledge about injectable contraceptives (60.0%), a positive attitude toward their use (68.6%), received spousal support (74.3%), perceived the role of health workers as good (80.0%), and stated that access to services was easily reachable (82.9%). These factors collectively contributed to the high interest and continued use of injectable contraceptives in the study area. These findings underscore the importance of involving husbands and ensuring that midwifery services are supportive and accessible to sustain family planning programs in rural settings.